Automotive suspension and steering systems - Knowles, Don (Thomson Delmar Learning, 2002)
Today's Technician: Automotive Suspension and Steering, 3E continues to strike the perfect balance between theory and practice. The new edition of this tightly coordinated Classroom/Shop Manual package is guaranteed to guide users to the expertise they need to diagnosis and service suspension and steering systems on today's cars, SUVs, and light-duty trucks. Unmatched for completeness, this edition now offers opportunities to explore the latest advancements in suspension and steering technology, including: run-flat tires, shock absorber mountings on SUVs, the effect of 42V electrical systems on power steering pumps, electronic power and four-wheel steering systems, and new wheel alignment procedures. Shop safety, including procedures for handling hazardous waste, is stressed